DESIGN THINKING: THEORETICAL FOUNDATIONS AND CRITICISM - Косенко, Д. Ю.; Вишневська, О. В.; Остапик, С. В. (Art and Design, 2023)
Purpose: identifying the background of the design-thinking approach and analyzing critical caveats from the point of view of this background. Methodology. Structural and logical analysis based on literature analysis. Results. The theoretical foundations of design thinking in the context of general design methodology are studied. It was revealed that the features of the design thinking approach are primary attention to the “problem detection” procedure: solving the problem is relegated to the second place; and the deconstruction of the design process into separate small tasks, for the solution of which numerous methods, or “design-thinking tools”, are proposed, mostly heuristic. At the same time, it is noted that the theory of design thinking is unsystematic, does not contain clear criteria either for building design strategies, or for classifying and choosing methods, and thus cannot be called a methodology. Critical comments on the practice of design thinking are summarized. It has been proven that the reservations identified by the critics are not flaws, but caused by the underlying features of design thinking, and thus cannot be “fixed” without destroying the whole concept. Scientific novelty. For the first time, criticism of the design-thinking approach and the theoretical foundations of this approach are correlated, the essential grounds of critical comments are revealed. Practical significance. The results of the research can be used for the further development of the general design methodology, as well as in the teaching of relevant courses of design education.